Surface Strategy Taxonomy on EFL Learners’ Oral Presentation: A Study of Grammatical Error Analysis - Susilowati, Endang; Kusumaningtyas, Etika Dewi; Wafa, Zaenul (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Many Indonesian learners continue to struggle with learning English as a foreign language (EFL) and frequently produce errors in grammatical aspects when speaking English spontaneously. This may be influenced by several factors. Hence, this research reports on a study aimed at investigating and examining the errors produced by Indonesian learners in their oral presentations and the sources of the errors. In conducting this study, the error analysis procedures and a descriptive qualitative study were used. The data were collected from sixteen college students’ oral presentations of the non-English department. To gather the data, the students’ presentations were video-typed and the utterances were transcribed. In analysing the data, a theory of error classification proposed by Dulay et al. (1982) namely a surface strategy taxonomy was employed. The findings reveal that four types of errors based on the surface strategy taxonomy namely omission, addition, misformation, and misordering errors are found in the students’ productions in their oral presentation. The frequent errors made by the learners are omission, followed by misformation, addition, and misordering. Meanwhile, two major causes driving learners to make numerous mistakes are intra-lingual and inter-lingual interference. However, from both factors, the largest cause is intra-lingual interference. Thus, the students’ L1 interference affects their mastery of the target language. Finally, this study is expected to contribute to the improvement of EFL teaching and learning.